Different Electrodes Connections in Electrocoagulation of Synthetic Blow down Water of Cooling Tower - Anwer, Enas Ali; Abdul Majeed, Basma A. (Iraqi Journal of Chemical and Petroleum Engineering, 2020)
In this research, the performance of electrocoagulation (EC) using aluminum (Al) electrodes with Monopolar- parallel (MP-P), and bipolar - series (BP-S) arrangement for simultaneous removal of dissolved silica, and hardness ions (calcium, and magnesium) from synthetic blowdown water of cooling tower were investigated. The effects of current density, initial pH and time of electrolysis on the removal efficiency were studied in a batch stirred unit to find out the best-operating conditions. The obtained results for each target species are evidence that BP-S approach is the best for both electrodes configuration operated at a Current density of 1mA/cm2 through 30 min of treatment and pH=10 with the removal of 60 %, 97% and 98% for calcium, magnesium and silica, respectively. This arrangement required an electrical energy consumption of1.8 kWh/m3 which is higher than observed in a parallel arrangement.